Frequency of Exercise Induced Myocardial Ischemia in Asymptomatic Diabetic Patients - Bajracharya, Manil (Nepalese Heart Journal, 2008)
This is a cross sectional study of consecutive patients attending out patient departments of Bir Hospital and Sahid Gangalal National Heart Center, Kathmandu. The study was conducted between May 2004 and November 2005. Detailed history was taken from each patient. The patients underwent physical examination, biochemical tests, chest x-ray, resting ECG and a screening echocardiogram prior to undergoing an exercise stress electrocardiography(ESE). The inclusion criteria were diabetic patients with normal resting ECG and a screening echocardiagram prior to undergoing an exercise stress electrocardiography.